The Effects of Angiotensin Receptor-Neprilysin Inhibition on Major Coronary Events in Patients With Acute Myocardial Infarction: Insights From the PARADISE-MI Trial. Issue 23 (2nd November 2022) - Mehran, Roxana; Steg, Philippe Gabriel; Pfeffer, Marc A.; Jering, Karola; Claggett, Brian; Lewis, Eldrin F.; Granger, Christopher; Køber, Lars; Maggioni, Aldo; Mann, Douglas L.; McMurray, John J.V.; Rouleau, Jean-Lucien; et al.
Abstract : Background: In patients who survive an acute myocardial infarction (AMI), angiotensin-converting enzyme inhibitors decrease the risk of subsequent major cardiovascular events. Whether angiotensin-receptor blockade and neprilysin inhibition with sacubitril/valsartan reduce major coronary events more effectively than angiotensin-converting enzyme inhibitors in high-risk patients with recent AMI remains unknown. We aimed to compare the effects of sacubitril/valsartan on coronary outcomes in patients with AMI. Methods: We conducted a prespecified analysis of the PARADISE-MI trial (Prospective ARNI vs ACE Inhibitors Trial to Determine Superiority in Reducing Heart Failure Events After MI), which compared sacubitril/valsartan (97/103 mg twice daily) with ramipril (5 mg twice daily) for reducing heart failure events after myocardial infarction in 5661 patients with AMI complicated by left ventricular systolic dysfunction, pulmonary congestion, or both. In the present analysis, the prespecified composite coronary outcome was the first occurrence of death from coronary heart disease, nonfatal myocardial infarction, hospitalization for angina, or postrandomization coronary revascularization. Results: Patients were randomly assigned at a median of 4.4 [3.0–5.8] days after index AMI (ST-segment–elevation myocardial infarction 76%, non–ST-segment–elevation myocardial infarction 24%), by which time 89% of patients had undergone coronary reperfusion. Compared with ramipril, sacubitril/valsartan decreased the risk of coronary outcomes (hazard ratio, 0.86 [95% CI, 0.74–0.99], P =0.04) over a median follow-up of 22 months. Rates of the components of the composite outcomes were lower in patients on sacubitril/valsartan but were not individually significantly different. Conclusions: In survivors of an AMI with left ventricular systolic dysfunction and pulmonary congestion, sacubitril/valsartan—compared with ramipril—reduced the risk of a prespecified major coronary composite outcome. Dedicated studies are necessary to confirm this finding and elucidate its mechanism. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02924727.